The Bacterial Community Structure and Microbial Activity in a Traditional Organic Milpa Farming System Under Different Soil Moisture Conditions - Moreno-Espíndola, Iván P.; Ferrara-Guerrero, María J.; Luna-Guido, Marco L.; Ramírez-Villanueva, Daniel A.; De León-Lorenzana, Arit S.; Gómez-Acata, Selene; González-Terreros, Elizabeth; Ramírez-Barajas, Blanca; Navarro-Noya, Yendi E.; Sánchez-Rodríguez, Luis M.; Fuentes-Ponce, Mariela; Macedas-Jímenez, Juan U.; et al. (Frontiers in Microbiology, 2018)
Agricultural practices affect the bacterial community structure, but how they determine the response of the bacterial community to drought, is still largely unknown. Conventional cultivated soil, i.e. inorganic fertilization, tillage, crop residue removal and maize (Zea mays L.) monoculture, and traditional organic farmed soil “milpa”, i.e. minimum tillage, rotation of maize, pumpkin (Cucurbita sp.) and beans (Phaseolus vulgaris L.) and organic fertilization were sampled. Both soils from the central highlands of Mexico were characterized and incubated aerobically at 5% field capacity (5%FC) and 100% field capacity (FC) for 45 days, while the C and N mineralization, enzyme activity and the bacterial community structure were monitored. After applying the different agricultural practices three years, the organic C content was 1.8-times larger in the milpa than in the conventional cultivated soil, the microbial biomass C 1.3-times, and C and N mineralization 2.0-times (mean for soil incubated at 5%FC and FC). The dehydrogenase, urease, protease and acid phosphatase activity was higher in the conventional cultivated soil than in the milpa soil incubated at 5%FC and similar when incubated at FC. The relative abundance of Gemmatimonadetes was larger in the conventional cultivated soil than in the milpa soil in soil both at 5%FC and FC, while that of Bacteroidetes showed an opposite trend. The relative abundance of other groups, such as Nitrospirae and Proteobacteria, was affected by cultivation technique, but controlled by soil water content. The relative abundance of other groups, e.g. FBP, Gemmatimonadetes and Proteobacteria, was affected by water content, but the effect depended on agricultural practice. For soil incubated at FC, the xenobiotics biodegradation and metabolism related functions were higher in the milpa soil than in the conventional cultivated soil, and carbohydrate metabolism showed an opposite trend. It was found that agricultural practices and soil water content had a strong effect on soil characteristics, C and N mineralization, enzyme activity, and the bacterial community structure and its functionality. The effect of soil water content on the bacterial community was defined often by the cultivation technique.